Size and Density of Artemisia annua Stomata Soaked in Water Extract of Gloriosa superba Seeds - Rahmawati, Sri Indah; Yunus, Ahmad; Susilowati, Ari (Biosaintifika: Journal of Biology & Biology Education, 2017)
Artemisia annua is a herbaceous plant that produces artemisinin as a malaria drug, haemorrhoids therapy, aromatherapy, antiviral, anticancer and antibacterial. Gloriosa superba is a plant that contains high colchicine compounds, especially on the seeds. Gloriosa superba extracts of tubers, stems, seeds, and leaves were used as biomutagen for many plants. Colchicine contains of these plants as antimitotic have been studied and proven by the mitotic index plants. Water extracts of Gloriosa superba seeds was used as a mutagen for Artemisia annua. The aim of this study was to determine the size and density of Artemisia annua stomata soaked in water extract of Gloriosa superba seeds as a mutagen. Extraction of Gloriosa superba seeds obtained naturally on Krakal Beach, Gunung Kidul by using a maceration method with water solvent (1:1). Artemisia annua sprouts were obtained from B2P2TOOT Tawangmangu. Variables treatment on sprouts using water extract concentration of Gloriosa superba seeds and soaking time of Artemisia annua sprouts. Measurements of stomatal length, width and density were conducted in epidermis of Artemisia annua leaf. Observation and measurements of the stomata were conducted by using a light microscope. The results showed that the length and width of stomata were 0.025 mm and 0.017 mm respectively. The stomatal density of the control leaf (174.69 amount/mm2) was lower than the other treated plants. Stomatal size and density has increased with the increasing concentration extracts on treated plants. Water extracts of Gloriosa superba seeds proved the effects on stomatal size and density of treated plants.